Land cover dynamics of Oleshky Sands: time-series analysis 1987-2017 - Bogdanets, V. (Land Management, Cadastre and Land Monitoring, 2018)
Oleshky Sands is the largest expanse of sand in Ukraine and the second in Europe. In the beginning of XX century sands moving outside of arenas was almost stopped by planting trees (Pinus nigra ssp. pallasian and Pinus sylvestris L.), and the territory had different use during the years. A 30-year (1987-2017) time series of Landsat imagery obtained via USGS geoservice was used to reveal land cover dynamics of deserted landscapes of Oleshky sands using QGIS software. Heavy sand storms can impact nearby settlements and expose harmful effect on local industry and quality of life of local communities. Forest fire is another dangerous factor for protective forest plantations during last years. Our estimation shows that sandy areas increase during 2000-2017; generally, conservation measures had constant effect despite afforestation of last years. The preventive effect of forest on sands moving at Oleshky sands can be characterized as stable in case of constant care about the forest plantation and proper documentation on land use and ownership. Keywords: combating desertification, landscapes dynamics, land cover change, QGIS, Landsat imagery